Installing Flower Strips to Promote Pollinators in Simplified Agricultural Landscapes: Comprehensive Viability Assessment in Sunflower Fields - Jorge Ortega-Marcos; Violeta Hevia; Ana P. García-Nieto; José A. González (Land, 2022)
The installation of flower strips in simplified agricultural landscapes has been promoted as a tool to improve pollination services. While the effectiveness of flower strips in increasing pollinator visitation and yield is well-established, the social and economic feasibility of this measure remains unclear. Here, we evaluated the economic efficiency and social feasibility of installing flower strips to promote pollination under different scenarios of subsidy. A 2-year experiment was implemented by comparing sunflower fields with and without installed flower strips in central Spain, along with local farmer opinions obtained via a focus group. Flower strips significantly increased wild bee visitation to sunflower heads in the second year after implementation, with seed set being 11% higher on average in fields that had flower strips. Cost–benefit analysis revealed that investment in flower strips would be recovered by 4–5 years after installation, depending on the subsidy used. In the most favorable subsidy scenario, farmers could increase their annual benefits by 8.7% (29 €/ha) after recovering the initial investment. However, most local farmers did not perceive a significant increase in yield associated with the flower strip installation. The use of flower strips was negatively identified by farmers as a source of invasive weeds in adjacent fields, along with a lack of technical advice and economic incentives. Farmers fully agreed that direct economic subsidies were required for flower strips to be accepted as feasible approaches in the long-term.